Journalists Primed: How Professional Identity Affects Moral Decision Making - Ferrucci, Patrick; Tandoc, Edson C.; Schauster, Erin E. (Journalism practice, 2020)
This study examines whether professional journalists reason differently about moral problems when primed with their professional identity. This between-subjects experiment (N = 171) used the Defining Issues Test, a much-used and validated instrument that measures moral reasoning. The results show identity priming does not affect how journalists apply ethics. The study also found that journalists score far lower in moral reasoning than they did 13 years ago. These results are interpreted through the lens of social identity theory.